The stage- and sex-specific transcriptome of the human parasite Schistosoma mansoni - Sarah K. Buddenborg; Zhigang Lu; Geetha Sankaranarayan; Stephen R. Doyle; Matthew Berriman (Scientific Data, 2023)
Abstract The flatworm Schistosoma mansoni is an important but neglected pathogen that causes the disease schistosomiasis in millions of people worldwide. The parasite has a complex life cycle, undergoing sexual reproduction in a mammalian host and asexual replication in a snail host. Understanding the molecular mechanisms that the parasite uses to transition between hosts and develop into dimorphic reproductively competent adults may reveal new strategies for control. We present the first comprehensive transcriptomic analysis of S. mansoni, from eggs to sexually naïve worms. Focusing on eight life stages spanning free-living water-borne and parasitic stages from both intermediate and definitive hosts, we have generated deep RNA-seq data for five replicates per group for a total of 75 data sets. The data were produced using a single approach to increase the accuracy of stage-to-stage comparisons and made accessible via a user-friendly tool to visualise and explore gene expression ( https://lifecycle.schisto.xyz/ ). These data are valuable for understanding the biology and sex-specific development of schistosomes and the interpretation of complementary genomic and functional genetics studies.